The Program of All-Inclusive Care for the Elderly (PACE) in Improving Medical Surgical and Mental Health Care: a Literature Review - Kushariyadi (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Models of care services for the elderly in terms of medical surgical care and mental health need to be improved. Elderly with disabilities are at high risk of adverse health outcomes, and the best model of care has yet to be determined. A good holistic care model to empower every individual in society to improve the quality of care needs to be recommended. For example, comprehensive health care programs such as the Program of All-Inclusive Care for the Elderly (PACE) for adults and the elderly. The research objective was to determine the effectiveness of PACE in improving medical-surgical care and mental health. The search strategy for English-language studies relevant to the topic was carried out using the ScienceDirect database, limited from 2011 to 2021. The keywords used were “PACE”, “Medical Surgical Treatment”, “Mental Health”, “elderly”. Article full text reviewed to select studies that fit the criteria. The inclusion criteria in this review are: the nursing service program model, namely PACE. The search used the keywords above with the ScienceDirect database that matched the inclusion criteria for only 7 articles. The PACE service model improves services in Medical Surgical and Mental Health care, and implement a collaborative care model using a comprehensive interdisciplinary team.